Sustainable Tannin Gels for the Efficient Removal of Metal Ions and Organic Dyes - Koopmann, Ann-Kathrin; Ehgartner, Caroline Ramona; Euchler, Daniel; Claros Vargas, Martha Carmiňa; Hüsing, Nicola (MDPI, 2023)
The usage of a highly efficient, low-cost, and sustainable adsorbent material as an industrial wastewater treatment technique is required. Herein, the usage of the novel, fully sustainable tannin-5-(hydroxymethyl)furfural (TH) aerogels, generated via a water-based sol-gel process, as compatible biosorbent materials is presented. In particular, this study focusses on the surface modification of the tannin biosorbent with carboxyl or amino functional groups, which, hence, alters the accessible adsorption sites, resulting in increased adsorption capacity, as well as investigating the optimal pH conditions for the adsorption process. Precisely, highest adsorption capacities are acquired for the metal cations and cationic dye in an alkaline aqueous environment using a carboxyl-functionalized tannin biosorbent, whereas the anionic dye requires an acidic environment using an amino-functionalized tannin biosorbent. Under these determined optimal conditions, the maximum monolayer adsorption capacity of the tannin biosorbent ensues in the following order: Cu2+ > RB > Zn2+ > MO, with 500, 244, 192, 131 mg g(-1), respectively, indicating comparable or even superior adsorption capacities compared to conventional activated carbons or silica adsorbents. Thus, these functionalized, fully sustainable, inexpensive tannin biosorbent materials, that feature high porosity and high specific surface areas, are ideal industrial candidates for the versatile adsorption process from contaminated (heavy) metal or dye solutions.

The usage of a highly efficient, low-cost, and sustainable adsorbent material as an industrial wastewater treatment technique is required. Herein, the usage of the novel, fully sustainable tannin-5-(hydroxymethyl)furfural (TH) aerogels, generated via a water-based sol-gel process, as compatible biosorbent materials is presented. In particular, this study focusses on the surface modification of the tannin biosorbent with carboxyl or amino functional groups, which, hence, alters the accessible adsorption sites, resulting in increased adsorption capacity, as well as investigating the optimal pH conditions for the adsorption process. Precisely, highest adsorption capacities are acquired for the metal cations and cationic dye in an alkaline aqueous environment using a carboxyl-functionalized tannin biosorbent, whereas the anionic dye requires an acidic environment using an amino-functionalized tannin biosorbent. Under these determined optimal conditions, the maximum monolayer adsorption capacity of the tannin biosorbent ensues in the following order: Cu2+ > RB > Zn2+ > MO, with 500, 244, 192, 131 mg g(-1), respectively, indicating comparable or even superior adsorption capacities compared to conventional activated carbons or silica adsorbents. Thus, these functionalized, fully sustainable, inexpensive tannin biosorbent materials, that feature high porosity and high specific surface areas, are ideal industrial candidates for the versatile adsorption process from contaminated (heavy) metal or dye solutions.
Sustainable Tannin Gels for the Efficient Removal of Metal Ions and Organic Dyes
Keywords: adsorption; biosorbent; porous materials; tannin; metal complexation; adsorption; biosorbent; porous materials; tannin; metal complexation